Development of a liquid N fertilizer from an agro-industrial effluent - Riaño,B. (2022)
Abstract Anaerobic digestion (AD) has been largely studied and it is widely applied for manure treatment in Europe, although its implementation is scarce in Spain and Portugal. The major benefit of AD is the production of renewable energy in the form of methane and digestate that is used as fertilizer, as it contains N, P and K. The aim of this work was to use gas-permeable membrane technology to capture N from slurry co-digested with orange peel residue, obtaining a liquid solution of ammonium sulfate that has been tested as a fertilizer in micropot trials. The data obtained show a recovery of 62% of the N from the digestate, and a recovery rate of N of 43.0 ± 6.6 g N per m2 of membrane and per day. The results of the micropot test showed that the liquid ammonium sulfate solution had a fertilizing effect similar to that of the mineral N fertilization.